Kebutuhan Sarana Transportasi Umum Dilihat Dari Bangkitan Sistem Pergerakan Antar Wilayah di Kabupaten Natuna Berdasarkan Data Asal Tujuan Transportasi Tahun 2006 - Maimunah, Siti; Sonny, Imam (Warta Penelitian Perhubungan, 2011)
Transportation which serves as a driving force for development (promoting function) is expected to be precise in formulating planning as needed. The purpose of the study is to plan public transportation needs for community Natuna district to other areas. The purpose of the study is to obtain the number of public transportation needs for community Natuna district in the future. By using the method of Furness and based on data from the Origin Destination Survey in 2006, then in 2012, there has been growth in the movement of 3 % with the use of the main mode of sea transportation by 52 % . With the application of hub and spokes pattern in the cross-shipping, it can synergize with the application of force on the island of Natuna district and makes the distribution of service load is spread evenly across the district capital. Development of assistive technologies such as port infrastructure so as a mode of captive to the small islands can be improved reliability.Keywords: transportation needs, Furness